The same and the other: Beckett's The unnameable, Derrida and Levinas - A. Uhlmann (Law Text Culture, 1997)
In an article concerning the Mabo decision of the Australian High Court Paul Patton discusses Deleuze's notion of the problem-field around which structures are formed (Patton, 1995: 90). Events are themselves differences in that, like the present which repeats itself but is always a different present, the events which occur in our world are always different from one another. They are the things which happen in the world, the things which have happened and which are happening now and it is this series of happenings which define who we are. Deleuze further considers that, like an animal adapting to a given environment, events happen around problems and it is the problems which define the shape of a given society.